2008
DOI: 10.1007/s10812-009-9117-y
|View full text |Cite
|
Sign up to set email alerts
|

Combination method for monitoring the characteristics of aqueous suspensions of metallic nanoparticles

Abstract: We have used a combination of physical diagnostics methods (laser probe, absorption spectroscopy, transmission electron microscopy) to study an aqueous suspension of silver nanoparticles, formed by laser ablation of a metal target in the atmosphere. We have established that application of the methods described allows us to obtain the most complete information about the state of nanosized metal particles in optically transparent media.Key words: aqueous suspension of metal nanoparticles, laser ablation, laser p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…Furthermore, Fig. 1b and d shows red shifts of λ max that were mentioned several times in the literature [2,3,6,7,16] and are due to a reduction of electron density on the particle surface as their size increases.…”
Section: Modeling Extinction Of Aqueous Ag and Ausupporting
confidence: 54%
“…Furthermore, Fig. 1b and d shows red shifts of λ max that were mentioned several times in the literature [2,3,6,7,16] and are due to a reduction of electron density on the particle surface as their size increases.…”
Section: Modeling Extinction Of Aqueous Ag and Ausupporting
confidence: 54%
“…As a result, the SPR spectrum experiences a red shift. It must be noted that a red shift caused by aggregation over time of Ag particles in colloidal solutions has been reported [9]. This was not typical of the sample containing PVA and indicated that colloidal solutions of Ag are more stable in the presence of PVA.…”
mentioning
confidence: 91%
“…This enables the most complete information about the state and properties of the metal nanophase to be obtained [9]. In the present work, we used transmission electron microscopy (TEM), single-wave laser probing of transparent ultradispersed media, and SPR absorption spectroscopy for these purposes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in [3,7] evaluate the basic parameters of the evolving ultrafine phase, according to them the size of particles belongs to the nanometer range of 30-140 nm and shows the relatively high level of concentration (10 11 -10 13 cm −3 ). According to research works [8,9], the technique of laser synthesis can penetrate the metal nanoparticles formed in the ELT in optically clear solution, thereby forming colloidal systems of the treated metal material.…”
Section: Methodsmentioning
confidence: 99%